2007
DOI: 10.1055/s-2007-966269
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between referral indications for open-access upper gastrointestinal endoscopy and endoscopic findings?

Abstract: General practitioners' referral indications for open-access endoscopy did not add any relevant predictive value for endoscopic findings in comparison with what might have been expected from overall prevalence. Only alarm symptoms slightly increased the probability of finding cancer and only reflux-like symptoms slightly increased the probability of finding reflux esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…On the other hand, the percentage of patients with normal endoscopic findings showed a rapid increase over the years. In addition, endoscopic findings rarely alter therapy, since most patients with dyspeptic symptoms receive acid-suppressive treatment after endoscopy anyway (17,18). Therefore, we suggest that patients who have dyspepsia without alarm symptoms, clinical characteristics and H. pylori infection should not initially undergo an upper GI endoscopy.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the percentage of patients with normal endoscopic findings showed a rapid increase over the years. In addition, endoscopic findings rarely alter therapy, since most patients with dyspeptic symptoms receive acid-suppressive treatment after endoscopy anyway (17,18). Therefore, we suggest that patients who have dyspepsia without alarm symptoms, clinical characteristics and H. pylori infection should not initially undergo an upper GI endoscopy.…”
Section: Discussionmentioning
confidence: 97%
“…16 Diagnostic performance for failure of antacid medication from three studies [22][23][24] showed a low association with oesophagogastric cancer (Table 2).…”
Section: Other Symptomsmentioning
confidence: 99%
“…Criteria for referral were most commonly listed for suspected colorectal cancer[8, 10, 12, 13, 15-20, 22, 23, 25, 27, 28, 30, 31, 33, 35, 36, 38, 40]. Other GI conditions for which some referral criteria were found included suspected upper GI cancer[9, 24, 25, 27-30, 38, 39], hepatitis[11, 14, 26, 30], and functional disorders such as irritable bowel syndrome, dyspepsia, diarrhoea and constipation[21, 30, 32, 34, 37]. We found four papers on the management of a variety of important GI conditions, but they did not contain criteria for referral: inflammatory bowel disease[42], pancreatitis [43-44] and acute gastrointestinal blood loss[45].…”
Section: Resultsmentioning
confidence: 99%
“…Negative predictors of cancer were the presence of heartburn and having dysphagia for more than one year [24]. Another study concluded that alarm symptoms, defined as weight loss, dysphagia or melena/haematemesis, had a 4% positive predictive value for finding cancer, but that many patients with cancer identified using these guidelines are untreatable [39]. …”
Section: Resultsmentioning
confidence: 99%